PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR SISWA KELAS VIII DI SMPN 12 PADANG - Jumardi, Jumardi; Nurhuda, Ahmad; Syamdani, Syamdani (Pendidikan Sejarah, 2014)
Â This research was based on the less efficiency of using media in learning process. There were students who do not quite pay attention to the material which was taught by the teacher, and many students came and out to the class while the learning process go on. Based on the problem, this research was focused on influence of Visual Audio Media used toward students learning achievement in history subject at VIII grade SMP Negeri 12 Padang. This research was aimed to find out the influence of Visual Audio Media use in history subject (IPS) learning achievement of students in VIII grade SMP N 12 Padang.Based on the problem, the type of this research was experiment research. The population of the research was the whole of students VII grade SMP N 12 Padang in semester 1 year 2013/2014. This research consisted of two sample classes, that were Experiment Class and Control Class by total sampling design.The findings if this research showed that there was influence of using learning method with Visual Audio Media toward students achievement at VIII grade SMP N 12 Padang. The learning achievement of Experiment class that used Visual Audio Method was higher than learning achievement of control class that used speech learning method (ceramah). The average result of class experiment was 85,54 and in the class control was 75,29. Based on the result, it showed that the average result of students in the class experiment was higher than in the control class.Based on the explanation above, it could be concluded that using Visual Audio Media in learning history (IPS) had influence toward learning achievement, which could be seen from the value of experiment class which higher than control class.